PENINGKATAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) PADA MATERI KOMPOSISI DAN DEKOMPOSISI BANGUN DATAR KELAS 4 SDN PENGKOL 01 TAHUN AJARAN 2023/2024 - Farikhah Lely Fitria; Veronika Unun Pratiwi; Agus Sri Antana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to improve the learning outcomes of Mathematics Material Composition and Flat Build Composition with the Numbered Head Together (NHT) Learning Model in students of grade IV SDN Pengkol 01, Sukoharjo. This research is a class action research with a class IV research subject of SDN Pengkol 01 which totaled 24 participants. The research model uses 4 stages, namely, planning, action, observation and reflection. The data collection technique in this study uses data collection instruments in the form of tests. The data analysis technique in this study uses the percentage of students' learning outcomes. The results of the research concluded that: Mathematics Learning of Composition Materials and Flat Building Composition using the Numbered Head Together (NHT) class IV SDN Pengkol 01 Sukoharjo learning model, can improve students' learning outcomes. The increase in learning outcomes can be seen from the increase in the average learning outcomes of students and the percentage. In the pre-cycle stage the average student learning outcome score was 65.83%, in cycle I the average student learning outcome score increased to 70.41%, and in cycle II the average student learning outcome score increased to 100%.